Problemy społeczne Galicji Zachodniej w początkach II Rzeczypospolitej (wybrane zagadnienia) - Przeniosło, Marek (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
In the first months of the regained independence Polish lands experienced serious social and economic problems. So it was in Western Galicia. The most urgent issues were to secure food supplies and take organized care of the people who found themselves in a difficult situation (poverty, unemployment). In Western Galicia the responsibility for social assistance was largely taken by the Polish Liquidation Committee which closely collaborated on a number of issues with local governments and various organizations. The main obstacles in providing active assistance were limited financial resources and the difficulties in gathering the required amount of food. Despite the rather serious food shortages in West Galicia there were no cases of prolonged shortages of basic foodstuffs, such that could jeopardize life and health of the public on a larger scale. The disorganized labor market needed a lot of intensive initiative. Similarly to other Polish lands, at the beginning of independence Western Galicia had to face high crime rate. It partly resulted from the weakening of the security service and the ineffectiveness of judicial authorities. Another issue which destabilized the social order were ethnic conflicts.